A BRIDGE IN TWO MEDITERRANEAN COUNTRIES: THOSE WHO LEARN TURKISH IN ITALIAN SOCIETIES: - Çelik, Gamze (International Online Journal of Education and Teaching, 2022)
Learning a foreign language enables people to get to know different cultures. People who know different cultures get richer. So, their prejudices against people are destroyed. Thus, a foreign language student may both improve himself and become a better person. In this context, the aim of the present study is to learn the thoughts of Turkish language learning Italians. The first sub-aim of the research is to determine the similarities and differences between the Turkish language and the Italian language. The second sub-aim is to learn what expectations Italians have while learning Turkish. In this study, qualitative research method was used to find answers to the above questions. In the current study, case study design was used. The interviews were analyzed through qualitative data analysis. Participants were determined using the Analogous (Homogeneous) sampling method among Italians who know or learn Turkish. Italians stated that they learned Turkish both by attending the course and by their own efforts. Italians especially have difficulty learning the sounds "h, ğ, ğı and ı". According to the results of the research, Italians who learn Turkish generally try to learn our language because they need it and because they love Turkish.